Characterization of Bifidobacteria from infant feces with different mode of birth at Purwokerto, Indonesia - PANCRASIA MARIA HENDRATI; DYAH FITRI KUSHARYATI; DINI RYANDINI; OEDJIJONO OEDJIJONO (Society for Indonesian Biodiversity, 2017)
Hendrati PM, Kusharyati DF, Ryandini D, Oedjijono. 2017. Characterization of Bifidobacteria from infant feces with different mode of birth at Purwokerto, Indonesia. Biodiversitas 18: 1265-1269. Bifidobacteria belongs to the so-called beneficial intestinal flora. Before attempting to raise their intestinal levels to improve the health status of the host, it is importance to know about physiological variations in the Bifidobacterial colonization of the human intestine. Birth process influenced the diversity of Bifidobacteria in infant feces. This research was intended to isolate and characterize Bifidobacterium spp. as well to evaluate their presence in the feces of infants who were born by mode of normal, caesarean and premature. The research was conducted by survey method and data were analyzed with descriptive analysis. Bifidobacterium character was observed include colony and cell morphology. The biochemical test included catalase, oxidase, indole, Voges-Proskauer, different pH growth, and resistance to lysozyme. Bifidobacterium metabolites obtained tested its bacterial activity to Salmonella typhimurium and Escherichia coli. The result of this research showed that 35 isolates are suspected Bifidobacterium group and after API 20 A test showed 17 isolates are rally genera of Bifidobacterium spp.and all isolates come from infant feces with caesar and premature delivery. These isolates inhibited the growth of S. typhimurium and E. coli with different inhibitory capabilities. This finding is very important for science and medical point of view and could be developed with further research.